Weight loss trends in women`s wrestling and potential implications of menstrual cycle: a narrative review - Jagim, A. R.; Fields, J. B.; Jones, M. T. (Nutrients, 2026)
Background/Objectives: Women`s wrestling is one of the fastest growing sports within the United States at the high school and collegiate level. Weight-class sports, such as wrestling, present unique challenges for female athletes, particularly in managing acute weight fluctuations associated with the menstrual cycle. However, less is known regarding how sex-specific physiology may influence weight management strategies among female wrestlers. The purpose of this review was to highlight current weight loss trends among high school and collegiate female wrestlers and summarize the physiological mechanisms driving potential menstrual-related fluid retention and subsequent changes in body mass or composition.